WANPRESTASI ANGGOTA DALAM PERJANJIAN PINJAM-MEMINJAM UANG PADA KOPERASI JAYA BORNEO DI KOTA PONTIANAK - JAKA DANIEL NIM. A1012181106 (Fakultas Hukum Universitas Tanjungpura, 2023)
Abstrac Cooperatives are people's business activities that are in great demand by the community, because it is enough with small, affordable capital that they can also help the economy of people who want to do business in the form of providing working capital, and/or other urgent needs. The Jaya Borneo Savings and Loan Cooperative (KSP) has 384 members and the community is traders in South Pontianak, Pontianak City, which has been established with legal entity number 145/BH/X dated 31 August 1998 and this cooperative always organizes RAT (Annual Members' Meeting) because there are default members of the cooperative.Based on the background of the problem, the formulation of the problem to be discussed in this study is